Testing the effectiveness of the culturally adapted skills training START NOW to reduce mental health problems in adolescent refugees: study protocol for a randomized controlled trial - Bacher, Janine; Stadler, Christina; Unternaehrer, Eva; Brunner, Donja (Frontiers in Public Health, 2024)
Background: Adolescent refugees are particularly vulnerable to mental health problems, as they experience many risk factors associated with their resettlement at crucial stages of their physical and emotional development. However, despite having a greater healthcare needs than others, they face significant barriers to accessing healthcare services. Therefore, this study aims to test the effectiveness of a low-threshold, culturally adapted version of the skills training START NOW -START NOW Adapted -in reducing mental health problems among adolescent refugees.Methods: We will recruit 80 adolescent refugees (15 to 18 years) with symptoms of anxiety and depression or high perceived stress in Northwestern Switzerland. They will be randomly assigned to one of two study groups: an intervention group, receiving START NOW Adapted, and a control group, receiving treatment as usual (TAU). The intervention will last 10 weeks and will consist of one-hour sessions per week provided by a trained facilitator with the same cultural background, in the respective language. Assessments to collect depressive and anxious symptoms, perceived stress, social-ecological resilience, and emotion recognition abilities will be conducted pre-intervention, post-intervention (11 weeks later) and at the 3-month follow-up. Multilevel models will be computed with primary and secondary outcome measures as dependent variables. An effect of at least moderate size will be considered clinically relevant.Discussion: This randomized controlled trial aims to investigate the effectiveness of a culturally adapted version of START NOW, providing valuable insights to improve current health promotion for adolescent migrants in Switzerland (or rather lack thereof). Ultimately, the effects of START NOW may facilitate integration and promote healthy development while decreasing costs associated with treating migration-or conflict-related trauma.Clinical Trial Registration: ClinicalTrials.gov, identifier: NCT06324864.